Fujita phenomenon in higher-order parabolic equation with nonlocal term. Issue 6 (26th April 2018) - Yang, Chunxiao; Ji, Feiyu; Yin, Qingyan
Abstract : This paper considers the Cauchy problem for a higher-order semilinear parabolic equation with nonlocal term in, where, , , and . We obtain the critical Fujita exponent to the problem, in the sense that every nontrivial solution blows up in finite time whenever, and there are both global and non-global solutions if .